Cooperative convex control of multiagent systems applied to differential drive robots - López-Estrada, Francisco-Ronay; Darias, Helen; Puig, Vicenç; Valencia-Palomo, Guillermo; Domínguez-Zenteno, Joaquin; Guerrero-Sánchez, María-Eusebia (Zielona Góra: Uniwersytet Zielonogórski)
This work proposes a convex cooperative control scheme for a multiagent system of differential mobile robots in a leader-follower formation. First, the kinematic model of the differential robots is obtained in a linear parameter varying representation. Next, a reference model approach is considered to track the desired trajectory. The paper`s contribution is then to derive conditions to guarantee the convergence of the convex controller, which is achieved using a non-quadratic Lyapunov function. Subsequently, this control law is integrated into the agent that leads a distributed control protocol based on graph theory designed to reach the consensus of the followers. Simulations of five mobile robots are performed to illustrate the effectiveness of the proposed method.
Keywords: convex control; multiagent systems; differential robots; tracking control